Black women’s oppositional gaze making images - Sales, Michelle (2020)
In this article, we consider the audio-visual production carried out by black women in Brazil since the second decade of the 21st century. Our objective is to propose a reflection, adopting an intersectional approach, on how an oppositional gaze creates images that break with racist stereotypes and challenge whiteness (hooks, 1992). We argue that the production of black women in Brazil questions the reproduction of institutional racism and digs deeper into the issue of colonial past. They create a narrative dispute that the oppositional feminine gaze imposes on the film industry.